DECIPHERING INHERITANCE PATTERN OF RESISTANCE TO FUSARIUM WILT DISEASE IN CASTOR (Ricinus communis L.) - C. LAVANYA, T. MANJUNATHA, S. VANISRI; B. VIDYA SAGAR, MANMODE DARPAN MOHANRAO, S. SENTHILVEL, M. SANTHA LAKSHMI PRASAD, M. SUJATHA (The Journal of Research, PJTSAU, 2022)
Castor is an important non-edible oilseed crop having varied industrial applications. Fusarium wilt caused by Fusarium oxysporum f. sp. ricini is a serious disease in castor. Chemical management of fusarium wilt is troublesome due to soil borne nature of the pathogen. Utilization of genetic resistance is the best possible solution for management of fusarium wilt. The present study was aimed at genetic characterization of three resistant germplasm lines namely AP-70, AP-127 and AP-163. The resistant lines were crossed with a susceptible inbred, ‘JI-35’ to generate F1s and F2 populations. The parents, F1s and F2 individuals were screened for fusarium wilt resistance in the wilt sick plot maintained at ICAR-Indian Institute of Oilseeds Research, Hyderabad, India. The reaction of F1s indicated that the nature of fusarium wilt resistance in AP-70 and AP-163 is recessive while it is dominant in AP-127. The segregation of resistance and susceptibility in F2 populations showed that fusarium wilt resistance in AP-70 and AP-163 is conferred by two recessive genes involving complementary interaction while two dominant complementary genes governs fusarium wilt resistance in AP-127. The resistant lines used in the present study are largely underutilized in castor improvement leaving scope for its exploitation in widening the genetic base of breeding lines in castor improvement.